Round‐Robin Studies on Roll‐Processed ITO‐free Organic Tandem Solar Cells Combined with Inter‐Laboratory Stability Studies. Issue 4 (7th October 2014) - Livi, Francesco; Søndergaard, Roar R.; Andersen, Thomas R.; Roth, Bérenger; Gevorgyan, Suren; Dam, Henrik F.; Carlé, Jon E.; Helgesen, Martin; Spyropoulos, George D.; Adams, Jens; Ameri, Tayebeh; Brabec, Christoph J.; et al.
Abstract: Roll‐processed, indium tin oxide (ITO)‐free, flexible, organic tandem solar cells and modules have been realized and used in round‐robin studies as well as in parallel inter‐laboratory stability studies. The tandem cells/modules show no significant difference in comparison to their single‐junction counterparts and the use of round‐robin studies as a consensus tool for evaluation of organic solar cell parameters is judged just as viable for the tandem solar cells as for single‐junction devices. The inter‐laboratory stability studies were conducted according to testing protocols ISOS‐D‐2, ISOS‐D‐3, and ISOS‐L‐2, and in spite of a much more complicated architecture the organic tandem solar cells show no significant difference in stability in comparison to their single‐junction counterparts. Abstract : Birds of a feather: Round‐robin studies and parallel stability studies on indium tin oxide (ITO)‐free, flexible, roll‐processed organic tandem solar cells show no significant difference in comparison to their single junction counterparts. Round‐robin studies are thus judged to be just as viable for creating efficiency consensus about tandem devices as for single‐junction devices.